2016
DOI: 10.1111/anu.12461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DL-methionine supplementation on the success of fish meal replacement by plant proteins in practical diets for juvenile gibel carp (Carassius auratus gibelio)

Abstract: A ten-week feeding trail was conducted to investigate the effects of increasing DLmethionine (Met) supplementation on the success of fish meal (FM) replacement with plant proteins in practical diets for juvenile gibel carp, Carassius auratus gibelio. Twelve isoenergetic diets were formulated including two 150 g kg −1 FM diets (Diet 1-positive control 1 reflecting a commercial diet and Diet 2-positive control 2 reflecting a commercial diet but with balanced essential amino acid (EAA) profile) and ten 50 g kg −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Whole body moisture, protein, lipid, and ash contents were not influenced by dietary treatments in this study, which confirms that the total substitution of FM by PP in the diet for blunt snout bream has no adverse effect on the body composition. These finding are consistent with those obtained by Cai et al (), Zhou, Habte‐Tsion, Ge, Liu, et al (); (Zhou, Habte‐Tsion, Ge, Xie, et al, ) in the target species; by Ren et al () in gibel carp ( Carassius auratus gibelio ), and by Cabral et al () in Senegalese sole ( S. senegalensis ). In contrast, Hien et al () reported that the replacement of fishmeal by soy protein concentrate in the diet of snakehead ( Channa striata ) affected whole body moisture, lipid, and ash.…”
Section: Discussionsupporting
confidence: 92%
“…Whole body moisture, protein, lipid, and ash contents were not influenced by dietary treatments in this study, which confirms that the total substitution of FM by PP in the diet for blunt snout bream has no adverse effect on the body composition. These finding are consistent with those obtained by Cai et al (), Zhou, Habte‐Tsion, Ge, Liu, et al (); (Zhou, Habte‐Tsion, Ge, Xie, et al, ) in the target species; by Ren et al () in gibel carp ( Carassius auratus gibelio ), and by Cabral et al () in Senegalese sole ( S. senegalensis ). In contrast, Hien et al () reported that the replacement of fishmeal by soy protein concentrate in the diet of snakehead ( Channa striata ) affected whole body moisture, lipid, and ash.…”
Section: Discussionsupporting
confidence: 92%
“…The highest value of plasma ammonia contents was found in fish fed NC, while a decreased trend of TNA discharge amount into water was found in fish fed reduced dietary protein (Diets 1–4). The above results indicated that excess AA in the diet were not used for growth or protein deposition of Jian carp, but resulted in extra energy expenditure towards deamination and excretion as the previous reports in gibel carp (Ren et al, ). Similarly, in grass carp, TAN excretion in to water was reduced in plant‐based practical diets with the decrease in dietary protein level supplemented of lysine and methionine (Gan et al, ).…”
Section: Discussionsupporting
confidence: 76%
“…Plasma ammonia, glucose, total protein, albumin, total triglyceride concentrations and alanine aminotransferase (ALT) and aspartate transaminase (AST) activities were analysed using an automatic biochemical analyzer (Mindray BS‐400, Mindray Medical International Ltd., Shenzhen, China) as described in our previous studies (Ren et al, ). TAN analysis was according to the method by Gan et al ().…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with this view, studies performed to investigate the impact of extruded feed in the diet concluded that the extrusion might diminish the contents of antinutritional factor and the inhibitors (Adamidou et al, ; Barrows, Stone, & Hardy, ; Drew, Borgeson, & Thiessen, ; Francis, Makkar, & Becker, ), and improve the protein utilization (Gaylord, Barrows, & Rawles, ). Furthermore, other studies reported a superior growth performance in some fish species fed diets supplemented with EAA such as in Senegalese sole ( Solea senegalensis ; Silva, Espe, Conceição, Dias, & Valente, ) and gibel carp ( Carassius auratus gibeilo ; Ren et al, ). Lee () stated that the addition of amino acids to the diets containing the plant protein mix is required to balance the essential amino acid composition and make the diet similar to positive control diets.…”
Section: Discussionmentioning
confidence: 97%